2010
DOI: 10.1016/j.nurt.2010.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes and Epilepsy

Abstract: Summary: Astrocytes form a significant constituent of seizure foci in the human brain. For a long time it was believed that astrocytes play a significant role in the causation of seizures. With the increase in our understanding of the unique biology of these cells, their precise role in seizure foci is receiving renewed attention. This article reviews the information now available on the role of astrocytes in the hippocampal seizure focus in patients with temporal lobe epilepsy with hippocampal sclerosis. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(104 citation statements)
references
References 100 publications
2
99
0
3
Order By: Relevance
“…We demonstrated that a PPARc agonist can modulate the GSH system balance, and inhibit astrocyte activation, which may relate to an antioxidative mechanism as astrocytes support neurons with precursors for GSH synthesis [33] and release of GSH from astrocytes is neuroprotective. However, under epileptic conditions, astrocytes are not neurosupportive, but rather release proinflammatory cytokines and free radicals which accelerate neuronal loss [34]. Therefore, our data suggest that increased release of GSH by rosiglitazone plays a key role in attenuating oxidative damage in epileptic rats, potentially through its inhibitory actions on astrocyte activation.…”
Section: Discussionmentioning
confidence: 74%
“…We demonstrated that a PPARc agonist can modulate the GSH system balance, and inhibit astrocyte activation, which may relate to an antioxidative mechanism as astrocytes support neurons with precursors for GSH synthesis [33] and release of GSH from astrocytes is neuroprotective. However, under epileptic conditions, astrocytes are not neurosupportive, but rather release proinflammatory cytokines and free radicals which accelerate neuronal loss [34]. Therefore, our data suggest that increased release of GSH by rosiglitazone plays a key role in attenuating oxidative damage in epileptic rats, potentially through its inhibitory actions on astrocyte activation.…”
Section: Discussionmentioning
confidence: 74%
“…In epilepsy, astrocytes have been reported to transform into ''reactive astrocytes'' (Belluardo et al, 1996;Hansen et al, 1990;Pollen and Trachtenberg, 1970), which are morphologically characterized by increased volume in humans (Binder and Steinhauser, 2006;de Lanerolle et al, 2010;Kim et al, 2009Kim et al, , 2010 and by disorganized architecture of process tufts and domain overlapping in mice (Oberheim et al, 2008).…”
Section: Is Reactive Astrogliosis Replicated In Thementioning
confidence: 99%
“…Reactive astrogliosis occurs in response to all forms of CNS insults including trauma, infections, stroke, neurodegeneration, and epilepsy (1)(2)(3). In most cases, astrocytes become transiently hypertrophic and express high levels of intermediate filament proteins such as glial fibrillary acid protein (GFAP) 3 and vimentin (4,5).…”
mentioning
confidence: 99%